2023
DOI: 10.1007/s40675-023-00258-5
|View full text |Cite
|
Sign up to set email alerts
|

The Worldwide Prevalence of Sleep Problems Among Medical Students by Problem, Country, and COVID-19 Status: a Systematic Review, Meta-analysis, and Meta-regression of 109 Studies Involving 59427 Participants

Mohammed A. Binjabr,
Idrees S. Alalawi,
Rayan A. Alzahrani
et al.

Abstract: Purpose of Review Several studies have found that medical students have a significant prevalence of sleep issues, such as poor sleep quality, excessive daytime sleepiness, and inadequate sleep duration. The purpose of this review is to carefully evaluate the current research on sleep problems among medical students and, as a result, estimate the prevalence of these disturbances. The EMBASE, PsychINFO, PubMed/MEDLINE, ScienceDirect, Scopus, and Web of Science and retrieved article reference lists w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 165 publications
0
3
2
2
Order By: Relevance
“…The factor that a majority of our participants reported to have a major effect on their sleep was excessive workload (71.30%), followed by mental health (68%), and improper sleep hygiene (65%). Furthermore, the average reported duration of sleep on a normal day at university from our study was five hours and 18 minutes which is lower than that reported by the meta-analysis of 109 research papers at six hours 30 minutes hours [12].…”
Section: Discussioncontrasting
confidence: 84%
“…The factor that a majority of our participants reported to have a major effect on their sleep was excessive workload (71.30%), followed by mental health (68%), and improper sleep hygiene (65%). Furthermore, the average reported duration of sleep on a normal day at university from our study was five hours and 18 minutes which is lower than that reported by the meta-analysis of 109 research papers at six hours 30 minutes hours [12].…”
Section: Discussioncontrasting
confidence: 84%
“…En esa línea, la revisión de Jahrami et al (2022) evidenció una prevalencia estimada de problemas de sueño del 41.16 % en estudiantes procedentes de 49 países de los diferentes continentes del mundo. Asimismo, la problemática se habría incrementado enormemente en los estudiantes de medicina, tal como lo indican los resultados de un meta-análisis que halló una prevalencia con estimación mundial del 57 % para una mala calidad del sueño y de 33 % para la somnolencia excesiva durante el día (Binjabr et al, 2023).…”
Section: Problemática Del Sueño En Universitariosunclassified
“…For instance, in a global systematic review and meta-analysis study conducted on sleep disruption in medicine students and its relationship with impaired academic performance, 39.8% of them reported having poor sleep quality (93). The prevalence of poor sleep quality was 51.45% in the global systematic review and meta-analysis study on the prevalence of sleep problems among 59427 medical students from 109 Studies 19). However, the sub-group analysis in the current meta-analysis studies showed that the prevalence of poor sleep quality, specifically among African medical students was 60.33 (95% CI: 54.96-65.69).…”
Section: Associated Factors Of Poor Sleep Quality Among University St...mentioning
confidence: 99%
“…Poor sleep quality was found to be highly prevalent among medical students 55.64% according to a global meta-analysis study (19). A cross-sectional study was carried out in seven countries the Dominican Republic, Egypt, Guyana, India, Mexico, Pakistan, and Sudan, and the prevalence of sleep quality among university students was found to be 73.5% (20).…”
Section: Introductionmentioning
confidence: 99%